Investigation of Blank Cartridge Gun Harming Potential in Target Range of 0-5 cm - Kılıç, Serbülent; Cantürk, Gürol; Öğünç, Gökhan İbrahim (The Bulletin of Legal Medicine, 2017)
Aim: The aim of our study is to show through experiments harming potential of blank firing guns, which are known to be harmless mistakenly.Materials and Method: Two different types of blank firing guns were utilized to shot at chicken leg as a tissue simulant; at a distance of 0-5 cm. Results of the experiments were photographed and recorded in a digital platform.Contact shot at chicken leg caused full-thickness bone fracture and full-thickness tissue penetration. In contrast, correlation was not detected between dimensions of smoothing and tissue damage on the target. We think that the causes of results that have no correlation, as weather conditions, wind, temperature, defiency of blank cartridge guns.Findings and Conclusion: The results we had, studies and case reports about this subject in literature exhibit obviously harming potential of blank firing guns for human body. No significant correlation was determined between damage, diameter of soot and shot range in 0, 1, 2, 3, 4 and 5 cm. A new research about the correlation between damage, diameter of soot and different close range of shot can be performed in another study.
Keywords: firearm; Firearm; gun powder; contact shot; bone fracture; blank cartridge gun injuries; handgun